Use of Esophageal Hemoximetry to Assess the Effect of Packed Red Blood Cell Transfusion on Gastrointestinal Oxygenation in Newborn Infants - Vora, Farha M.; Gates, Judy; Gerard, Kimberley; Hanson, Shawn; Applegate, Richard L., II; Blood, Arlin B. (American Journal of Perinatology, 2017)
Objectives There are no widely accepted methods of continuously monitoring gut oxygenation in the newborn during packed red blood cell transfusion. We investigated the use of an orally inserted light spectroscopy probe to measure lower esophageal oxyhemoglobin saturations (eStO2) before, during, and after transfusion and made comparisons with abdominal near-infrared spectroscopy (NIRS) and superior mesenteric artery (SMA) flow.Study Design Thirteen neonates with corrected gestational ages ranging from 22 weeks, 0 day to 37 weeks, 5 days were enrolled. eStO2 and NIRS measurements were recorded continuously for a 25-hour period starting 1 hour prior to starting the 4-hour transfusion. Transabdominal ultrasound was used to measure SMA flow prior to, upon completion, and 20 hours after the transfusion.Results Twelve infants completed the study. eStO2 was well-tolerated and was weakly (r = 0.06) correlated (p < 0.001) with NIRS. Compared with NIRS, eStO2 demonstrated a markedly greater variation in oxyhemoglobin values. NIRS and SMA flow measurements did not change, while eStO2 increased from 48 ± 5% and 45 ± 5% in the pre- and intratransfusion periods to 57 ± 4% in the posttransfusion period (p = 0.03).Conclusion Measurement of eStO2 is feasible in neonates and may provide a continuous and sensitive index of rapid changes in mesenteric oxygenation in this patient population.
Keywords: hemoglobin oximetry; necrotizing enterocolitis; newborn; transfusion; mesenteric blood flow